STRATEGI KOMUNIKASI EFEKTIF MUSYRIFAH DALAM RESOLUSI KONFLIK DI MA’HAD TMI PUTRI AL-AMIEN PRENDUAN - Ghefira Syaliina Putri Kusuma; Tawvicky Hidayat (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
This study aims to analyze the effective communication approaches used by supervisor of dormitory in resolving conflicts at TMI Al-Amien Prenduan for Female Islamic Boarding School. Social conflicts in the boarding school environment often arise due to the diverse backgrounds of the pupils and the intensity of interactions. Supervisor of dormitory plays a crucial role in conflict management to create a harmonious atmosphere. This research employs a qualitative method with a case study approach. Data collection techniques include observation, interviews, and documentation. The study involves five supervisors and five pupils as research subjects. Data validity is ensured through source and theoretical triangulation. The findings indicate that conflicts at TMI for Female can be categorized into four types: intrapersonal, interpersonal, intra-group, and inter-group conflicts. To address these conflicts, supervisors applies effective communication principles based on five key aspects: respect (mutual respect), empathy (understanding others’ feelings), audible (clear and comprehensible speech), clarity (message transparency), and humble (modesty in communication). Supporting factors for effective communication include openness, trust, cooperation, responsiveness, the pesantren environment, and its cultural values. However, there are also obstacles, such as a lack of openness, shyness, and excessive anxiety. In conclusion, supervisors serves as a wise conflict resolver and a role model in effective communication. By understanding and applying appropriate communication strategies, musyrifah can foster harmonious and conducive social interactions among pupils in the boarding school